حيوية التكثيف الأسلوبي في الشعر المغاربي المعاصر - صالحي, سمية (University of Eloued جامعة الوادي, 2022)
استطاعت الحركة الشعرية المغاربية المعاصرة أن تفرض وجودها، وتصنع مقوماتها الخاصة ،حيث تمكنت من أن تصبغ عليه طابع الهوية المغاربية، وهذا بعد ظهور كوكبة من الشعراء الذين خاضوا غمار حركة الحداثة في الشعر وسعوا لتأسيس مبدأ التميز و الإبداع، بمنجزات تواكب مستجدات العصر ومتغيراته، لأنه ينطلق من مرجعية فكرية وحضارية متميزة باختلافاتها وتعددية مشاربها، ولكون المنطقة المغاربية خاضت الكثير من المتغيرات الحضارية عبر الأزمان، كل هذه التجاذبات الحضارية صقلت الإبداع الفني، وطبعت عليه مميزات الخصوصية والتفرد ،تُمثل أساسه وأصالته . The Maghreb poetic movement was able to develop its own components, as it was able to impose its presence and imbue it with the character of Maghreb identity، and this is after the emergence of a constellation of poets who fought in the midst of the modernity movement in poetry, as they sought to establish the principle of excellence and Creativity, with achievements that keep pace with the developments of the era and its variables, because it stems from an intellectual and civilization reference that is distinguished by its differences and the plurality of its trends, and because the Maghreb region has undergone many cultural changes through the ages, all these civilizational interactions refined artistic creativity, and imprinted on it the characteristics of privacy and exclusivity, representing its basis and originality.
مقال
Keywords: الحركة الشعرية ؛ الأسلوبية ؛ التكثيف ؛ الشعر المغاربي المعاصر ؛ الهوية المغاربية ؛ الحداثة.: Poetic movement; stylistics; condensation; contemporary Maghreb poetry; Maghreb identity; modernity.